2020
DOI: 10.1002/fsn3.1726
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of spent black tea by recovery of antioxidant polyphenolic compounds: Subcritical solvent extraction and microencapsulation

Abstract: Spent black tea (SBT), waste remaining after producing tea beverages, is potentially an underutilized source of antioxidant phenolic compounds. This study evaluated the integrated processes of subcritical solvent extraction of polyphenols from SBT followed by microencapsulation to improve the stability of obtained extract. Optimization of extraction conditions was carried out by response surface methodology for the best recovery of antioxidant phenolic compounds. Two variables [temperature (°C) and ethanol con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…These spectral changes have been documented as characteristics of the pectin–casein bonding which may be created due to the Maillard conjugation [ 27 , 28 , 29 ]. The results from X-ray diffraction and thermal stability in our previous study have also confirmed the formation of a pectin–caseinate complex [ 8 ]. Moreover, emerged new peaks at 1105 and 1018 cm −1 in SBT en presented a band at 1150 cm −1 (C–O stretching) in both SBT and SBT en and a mild shift in the peak of O–H stretching at 3290 cm −1 , and indicated that conjugation had occurred between the polyphenols and sodium caseinate–pectin during the encapsulation process ( Figure S1 ).…”
Section: Resultssupporting
confidence: 69%
See 4 more Smart Citations
“…These spectral changes have been documented as characteristics of the pectin–casein bonding which may be created due to the Maillard conjugation [ 27 , 28 , 29 ]. The results from X-ray diffraction and thermal stability in our previous study have also confirmed the formation of a pectin–caseinate complex [ 8 ]. Moreover, emerged new peaks at 1105 and 1018 cm −1 in SBT en presented a band at 1150 cm −1 (C–O stretching) in both SBT and SBT en and a mild shift in the peak of O–H stretching at 3290 cm −1 , and indicated that conjugation had occurred between the polyphenols and sodium caseinate–pectin during the encapsulation process ( Figure S1 ).…”
Section: Resultssupporting
confidence: 69%
“…The SBT was produced as described previously [ 8 ]. Briefly, black tea leaves were brewed in boiling water for 6 min (2 g/100 mL), then filtered to obtain the residue.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations